A consensus opinion amongst stakeholders as to benefits of obstructive sleep apnoea treatment for cardiovascular health. Issue 4 (4th October 2018) - Landry, Shane A.; Banks, Siobhan; Cistulli, Peter A.; Hamilton, Garun S.; Héraud, Laure; Kairaitis, Kristina; Lubke, Steven; Mukherjee, Sutapa; Roebuck, Teanau; Soda, Joesph; Umbers, Darren; Rajaratnam, Shantha M. W.; et al.
ABSTRACT: Background and objective: Obstructive sleep apnoea (OSA) is a prevalent sleep disorder associated with increased cardiovascular morbidity and mortality. Whether treatment of OSA improves cardiovascular risk remains controversial. Our aim was to determine a consensus opinion of key sleep medicine stakeholder groups as to the cardiovascular benefits of treating moderate–severe OSA. Methods: A multidisciplinary panel was assembled from representatives from the Australasian Sleep Association, Sleep Health Foundation, Australasian Sleep Technologists Association, the Sleep Health Foundation Business Council and the Sleep Disorders Australia patient support group. Three statements reflecting areas of controversy related to cardiovascular benefits of OSA treatment were created. A modified RAND/UCLA appropriateness methodology was applied determining the panel's level of consensus and agreement with each statement. Results: Voting results indicated the panel: (1) remained unsure whether moderate–severe OSA treatment improves rates of cardiovascular events/death, (2) agreed that moderate–severe OSA treatment improves blood pressure in patients with hypertension and (3) mostly agreed that moderate–severe OSA treatment improves left ventricular function in patients with heart failure . Consensus of opinion was achieved for statements (1) and (2), but was narrowly missed for statement (3). Conclusion: The panel believed that findings from large‐scale randomized trials indicate that treatment of moderate–severe OSA has not been established to improve cardiovascular event or morbidity/mortality rates. Strong evidence supports the ability of treatment to reduce blood pressure. Whilst many panel members believed that treatment improves left ventricular function, some were uncertain of the clinical significance of this secondary endpoint measure derived from lesser quality evidence. Abstract : Commissioned by the Australasian Sleep Association and the Sleep Health Foundation, this statement draws on a panel composed of key sleep medicine stakeholders, including clinicians, researchers, technologists, as well as industry and community groups, to provide consensus of opinion as to the cardiovascular benefits of treating moderate–severe obstructive sleep apnoea. See related  Editorial